CORE STABILITY TRAINING: ITS INFLUENCE ON THE BASKETBALL ATHLETES' PERFORMANCE - Balbido, Jenelyn; Corpus, Gineva; Cruda, John Lloyd; Malone, Jemaima; Gula, Louie Petere (MEDIKORA, 2025)
This study assessed the Performance of the Basketball Athletes’ who engaged Core Stability Training in Baybay City. The researcher used quasi-experimental research design to document and evaluate the respondents' performance correlated to the provided evaluation criterion. There are 30 respondents in the study that are basketball athletes in the school of Baybay City, and snowball sampling was utilized in selecting the participants respectively. There are two groups in all respondents. The first group was the respondents who engaged in core stability training, and the other group was those who did not engage in core stability training. They performed the core training exercises in the survey criterion: (push-ups, supine toe taps, shooting drills, sumo squats, quadruped opposite leg, and arm raise.) Given standard time, the researcher will record only the attained repetition. Independent sample t-test, Welch two-sample t-test, and Mann-Whitney t-test are used in analyzing the data, were utilized at a 5% significance level. Overall, the study's outcome reveals that there is an essential difference of the basketball athletes’ performances who engaged in core stability training and those who did not. It infers that those who engage in core training perform better and have strong stamina. Thus, it is recommended to indulge in core stability training as part of a basketball athlete's training routine.